PERLINDUNGAN HUKUM TERHADAP ANAK KORBAN KEKERASAN SEKSUAL - Melani Sukma Laido; Kindom Makkulawuzar; Jupri, Jupri (Fakultas Hukum Universitas Ichsan Gorontalo, 2024)
This research aims to determine legal protection for child victims of sexual violence in Gorontalo City as well as factors inhibiting legal protection for child victims of sexual violence in Gorontalo City. This research is empirical legal research, namely legal research that examines law by conceptualizing it as real behavior (actual behavior), as an unwritten social phenomenon, which is experienced by everyone in social life. The results of the research show that, First, legal protection for child victims of sexual violence refers to Law Number 35 of 2014 concerning Child Protection and Law Number 12 of 2022 concerning Criminal Acts of Sexual Violence which aims to provide protection for the dignity and honor of a child. Second, the obstacles in implementing legal protection for children who are victims of criminal acts of sexual violence in Gorontalo City in the research results are caused by several factors, namely internal factors of the child, factors of the victim's family, community factors, and factors or facilities. The recommendations in this research are (1) Legal protection for children as victims of sexual violence, apart from being carried out based on applicable law, the government must collaborate with all elements so that criminal acts of sexual violence can be prevented from an early stage. (2) The government must routinely carry out outreach and guidance to all parties and the community to prevent and dare to report suspected criminal incidents of sexual violence.